2018
DOI: 10.1111/ele.12975
|View full text |Cite
|
Sign up to set email alerts
|

The control of risk hypothesis: reactive vs. proactive antipredator responses and stress‐mediated vs. food‐mediated costs of response

Abstract: Inducible defences against predators evolve because they reduce the rate of direct predation, but this benefit is offset by the cost (if any) of defence. If antipredator responses carry costs, the effect of predators on their prey is partitioned into two components, direct killing and risk effects. There is considerable uncertainty about the strength of risk effects, the factors that affect their strength, and the mechanisms that underlie them. In some cases, antipredator responses are associated with a glucoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
156
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(168 citation statements)
references
References 90 publications
(251 reference statements)
5
156
0
Order By: Relevance
“…On average, grunts and snappers arrived on coral reefs and in sea fans long before any predators. Whether predation risk is "predictable" or chronic on coral reefs remains unknown, but our findings offer an interesting potential link to the predicted foodrisk effects as described in the "control of risk" hypothesis (Creel, 2018).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…On average, grunts and snappers arrived on coral reefs and in sea fans long before any predators. Whether predation risk is "predictable" or chronic on coral reefs remains unknown, but our findings offer an interesting potential link to the predicted foodrisk effects as described in the "control of risk" hypothesis (Creel, 2018).…”
Section: Discussionmentioning
confidence: 70%
“…Thus, the interaction between habitat features and the probability of predator detection and successful escape can result in altered prey risk‐associated behaviors and vigilance (Heithaus et al, ). It has been recently argued that predators may exact greater influences on prey behavior where predation risk is predictable (Creel, ). While we did not measure predictability of predation risk in our study, abundance of predators in certain habitats, a potential proxy for exposure, may have resulted in a pro‐active response of apprehensiveness toward the bait, although this remains speculative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bison could be constantly on the move in response to the ghost of predation past (Brown and Vincent , Le Saout et al 2015), regardless of current wolf presence in the landscape. In addition, other mechanisms, such as memory‐based foraging (Merkle et al 2014) or harassment by biting insects (Raponi et al ), could be implicated in bison's decision to leave a food patch. Nevertheless, for at least one season, our results demonstrate the role of predator distribution in triggering patch abandonment by prey as predicted by the shell game hypothesis (Mitchell and Lima ).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and empirical studies have shown that animals do commonly spend less time foraging in risky than in safer areas (Brown and Kotler ). Prey can also assess the local risk of predation and adjust the time spent in different areas of their home range to avoid periods when predators are most active (Valeix et al , Kohl et al ), or exhibit reactive responses, such as fleeing, following an encounter with predators (Courbin et al 2016). The risky places hypothesis predicts that prey will either avoid or spend less time in areas where predation risk is predictability high over the long term, while the risky times hypothesis predicts that anti‐predator behaviours will be triggered specifically when predators are in real‐time proximity of prey (Creel et al , Moll et al 2017).…”
Section: Introductionmentioning
confidence: 99%